PENGGUNAAN KAPUR CaCO3 PADA TANAH DASAR KOLAM IKAN BERBEDA UMUR DI DESA KOTO MESJID KABUPATEN KAMPAR - Saberina Hasibuan; Syafriadiman Syafriadiman; Tardilus Tardilus (Fakultas Perikanan dan Kelautan, Universitas Riau, 2012)
The research was conducted from April until June 2012 at Soil and WaterQuality Management Laboratory Fisheries and Marine Science Faculty of RiauUniversity. The aim of the research is to know effect of CaCO3 lime to the pondbottom soil of chemical fertility and the water quality. The method usedexperiment and randomized block designs with 1 factor is CaCO3lime, with 5level of treatments doses of CaCO3 lime from 0 g/m2, 6.67 g/m2, 56.00 g/m2,112.00 g/m2, and 168.00 g/m2, and 2 groups is new pond age (0-4 years old) andold pond age (5-10 years old).The result indicated that the some doses of CaCO3 lime to increase in pHsoil pond age 0-4 years and 5-10 years is 168.00 g/m2 (P4). These conditionsresulted increased of initial pH range from5.0-5.8to6.7-7.1, C-organic about0.75%, N-total of approximately 0.07%, KPK approximately3.2 to 3.8me/100g,C/N ratioaround10.0 to 11.1. Thewater quality improvementin bothagegroupsoccurred frompH 5.7to 7.7, increased of turbidity, hardness, increased ofdissolved oxygenat pond age5-10 years old and concentration ofnitrateinthepondage of 0-4 years old.Keywords : CaCO3lime, chemical fertility, soil quality, water quality